Rafard (SP) e a cultura da cana-de-açúcar: considerações sobre a urbanização e as relações sociais - Pereira, Anaíza Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
We intend to expose this paper a brief review about the social factors that include the capitalist system. Having the city of Rafard as our focus of study, we are going to analyze how agribusiness and migration have great political significance in this small town, and still are determining factors for socio-cultural training of its citizens, as well the formation and economic development of their own city. We are going to observe how a town with only 8.599 inhabitants is subjected to the laws dictated by capital through the interference of a large sugarcane agro industrial production unit present in its territory

Pretendemos com o presente trabalho expor uma breve análise acerca de fatores sociais que englobam o sistema capitalista. Tendo o município de Rafard como nosso foco de estudo, analisaremos como o agronegócio e as migrações têm grande importância política nessa pequena cidade e ainda são fatores determinantes para formação sócio-cultural de seus munícipes, bem como a formação e o desenvolvimento econômico da própria cidade. Observaremos como uma cidade com apenas 8.599 habitantes se sujeita as leis ditadas pelo capital através da interferência de uma grande Unidade de Produção Agroindustrial Canavieira presente em seu território
Keywords: Economia agrícola; Economia agrícola - Aspectos sociais; Cana-de-açúcar; Migração interna; Agroindústria; Geografia agrícola; Migração; Geografia urbana; Geografia humana; Rafard (SP); Agriculture -Economic aspects; Migration, Internal; Sugarcane; Agricultural industries; Agricultural geography